Ship's Fuzzy Domain – a Criterion for Navigational Safety in Narrow Fairways - Pietrzykowski, Zbigniew (Journal of navigation, 2008)
The concept of ship's domain plays an important role in navigating a ship. It is a criterion of safety in the process of making decisions by the navigator – in analyzing and assessing a navigational situation and in performing the right manoeuvre. This concept is particularly useful in restricted areas, including narrow fairways, which results from the fact that in such waters a manoeuvring area is restricted so that the criterion of the closest point of approach (CPA) cannot be used. This author has analyzed definitions of ship's domain and methods of its determination found in the literature on the subject. Then a method of navigational safety assessment using the fuzzy domain concept is proposed in reference to a ship in a restricted area. The concept and method of determination have been, respectively, defined and described. The method is based on relevant navigators' knowledge. The methods and tools for knowledge acquisition and representation make use of artificial intelligence. Ships and navigational areas of various size have been considered.